Avaliação da estabilidade de tensão em sistemas com elos de corrente contínua em redes eletricamente próximas - Sessa, Bruno da Cruz (2017)
The purpose of this dissertation is to analyze voltage stability within systems comprising DC links where inverter stations are connected to the same electrical network. This system configuration is known as multi-infeed. To undertake such an evaluation, static modal analysis methodology based on eigenvalue decomposition was applied. This method affirms the proximity of voltage instability and identification of critical points within the system. Further objectives of this dissertation include the implementation of corrective measures at critical points and the verification of their effectiveness. Moreover, the calculation and evaluation of various multi-infeed indexes were also addressed. The simulations were first implemented within a smaller limited system comprised of only two DC links, this to consolidate voltage stability concepts. Further simulations were then undertaken within the Brazilian Interconnected Power System, which will soon accommodate six DC links feeding four independent inverter stations interconnected by relatively low impedance.